Effects of unilateral, bilateral, and combined unilateral+bilateral complex resistance training on bench press and squat strength in adolescent boxers - Liu, Y.; Liu, X.; Geng, J. (Frontiers in Physiology, 2024)
Objective To assess the effects of 8 weeks of unilateral (UNI), bilateral (BI), and combined unilateral + bilateral (UNI + BI) resistance training on bench press and squat strength in adolescent boxers.